Synthesizing evidence and identifying knowledge gaps in the role of swine in Japanese encephalitis virus transmission: a rapid systematic review of the literature - Horton, V.; Hanthorn, C. J.; Dixon, A. L.; Edache, S. E.; Thackrah, A.; Mitzel, D.; Noronha, L.; Cohnstaedt, L. W.; Brown, V. R.; Mire, C.; Cernicchiaro, N. (Frontiers in Sustainable Food Systems, 2024)
The United States is considered a susceptible region with great potential for the introduction of the Japanese encephalitis virus (JEV) given the presence of competent mosquito vector species, susceptible maintenance avian hosts, large populations of susceptible domestic and feral swine, intensive travel and trade activities to and from JEV-endemic countries, similar climatic and environmental conditions to epidemic countries, and no active JEV surveillance in place. As pigs are considered JEV’s primary amplifying host, comprehensively reviewing the available body of evidence, and respective knowledge gaps, pertaining to the role of swine in JEV transmission can provide valuable guidance to decision-makers. Our objectives were to synthesize scientific literature on the role of domestic and feral swine in the transmission of JEV via a rapid systematic review and identify knowledge gaps to determine potential areas amenable for future research. A total of 3,638 records were initially identified. Data were extracted from 227 reports. Transmission of JEV occurs primarily via infected mosquitoes; however, some evidence of direct oronasal transmission between pigs has been reported. Despite pigs exhibiting a short-lived viremia, JEV has been demonstrated to persist longer in their tonsils. In sows, JEV infection may cause reproductive disorders, and although maternal antibodies can confer protection for several months under field conditions, naïve piglets can exhibit neurologic signs which may progress to wasting disease. Studies evaluating breed or sex reported no association with JEV seropositivity. Application of biosecurity practices and vector control are recommended as preventive measures against introduction and spread of JEV in swine farms. Although there is no JEV vaccine licensed for pigs in the United States, live attenuated vaccines were reported to elicit superior immunogenicity compared to inactivated vaccines used in endemic countries. Summarizing the current understanding of JEV infection in swine can guide researchers, stakeholders, and policymakers in prioritizing research efforts and developing effective countermeasures. This is particularly crucial in the event of an outbreak in the United States, where preemptive measures can help minimize the spread of the virus, safeguard both human and animal populations, and ensure the long-term sustainability of the swine production sector.